(untitled) (Journal of Plant Disease Sciences, 2019)
Trichoderma viride mutants which were applied against soil borne plant pathogens were found effective against these pathogens after application of different concentrations chemical mutagens of Ethyl Methyl Sulphonate (EMS) and Hydroxyl Amine (HA) i.e. @ 50, 100,150,200 and 250 µl/ml at time interval of 60 minutes. Ten T. viride mutants were obtained and tested for their antagonistic activities in vitro. Efficient mutants were tested up to six generation to check their stability. Among the mutants, four stable mutants viz.,TvME-4 (T4), TvMH-8 (T8), TvME 3 (T3) and TvMH-9 (T9) were proved as effective antagonists against Sclerotium rolfsii,where as In case of Rhizoctonia bataticola the mutants TvME-4 (T4), TvMH-8 (T8), TvME-3 (T3) and TvMH-10 (T10) showed maximum growth inhibition and Fusarium udum was also inhibited by mutants TvME-3 (T3), TvME-4 (T4), TvMH-9 (T9) and TvMH-8 (T8) .